2014
DOI: 10.5387/fms.2014-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of the Flexor Pronator Muscles as a Dynamic Stabilizer of the Elbow Against Valgus Force

Abstract: : Flexor pronator muscles (FPMs) play a key role in stabilizing the elbow joint against valgus forces. However, no studies have investigated the in vivo kinematics of FPMs against these forces on the elbow. This study aimed to clarify the in vivo contribution of each FPM as a dynamic stabilizer in a clinical situation.Twelve healthy volunteers participated in this study. Verbal informed consent was obtained from all subjects. The elbow was flexed to 90 degrees, and the forearm was placed in the neutral positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…The stress US study showed that healthy volunteers displayed 0.7 mm of change in the MJD as measured with non-stress and stress [17]. Another study demonstrated that the change in the MJD under loaded and loadedcontracted conditions of the FDS was 0.2 mm [14].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The stress US study showed that healthy volunteers displayed 0.7 mm of change in the MJD as measured with non-stress and stress [17]. Another study demonstrated that the change in the MJD under loaded and loadedcontracted conditions of the FDS was 0.2 mm [14].…”
Section: Discussionmentioning
confidence: 96%
“…Some anatomical studies reported that the FDS was the individual muscle best suited to provide medial elbow support because of its proximity and relatively large bulk among the FPMs [6,8]. Current in vitro research recognized that FDS activity had significant effects on MJD using stress US [14,17]. However, these studies overlooked the importance of assessing FDS activity of individual fingers, as opposed to the activity in all of them collectively, through grip motion; thus, it remained unclear which finger's FDS contraction contributed most to elbow stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress US study showed that healthy volunteers displayed 0.7 mm of change in the MJD as measured with non-stress and stress [17]. Another study demonstrated that the change in the MJD under loaded and loaded-contracted conditions of the FDS was 0.2 mm [14].…”
Section: Discussionmentioning
confidence: 97%
“…Some anatomical studies reported that the FDS was the individual muscle best suited to provide medial elbow support because of its proximity and relatively large bulk among the FPMs [6,8]. Current in vitro research recognized that FDS activity had significant effects on MJD using stress US [14,17].…”
Section: Discussionmentioning
confidence: 99%